Maintenance management and operation on dam / Khairur Zahirin Misngat. - Misngat, Khairur Zahirin (2008)
Maintenance Management and Operation on dam is a combination of several actions in which to retain or restore an item to perform its required function. It also the action to operational dam. Dam is one of the mega structures that need to maintain and operate so that not occur a great harm could cause dam collapse or ruined. If this problem happens it can cause flooding and destroy a property around the dam. The aim of this research is to study the maintenance management and operation system on dam. To achieve this aim, there are three objectives have been set, to study maintenance management system presently implemented at dam, to generally identify the common problem facing in maintenance management and operation and to identify the common defect and safety aspect on dam. To obtain the data the following knowledge acquisition methods were used by interview, questionnaire and archives.